Projecting the risk of mosquito-borne diseases in a warmer and more populated world- a multi-model, multi-scenario intercomparison modelling study - Colón-González, Felipe J.; Sewe, Maquins; Tompkins, Adrian; Sjödin, Henrik; Casallas García, Alejandro; Rocklöv, Joacim; Caminade, Cyril; Lowe, Rachel (The lancet. Planetary health, 2021)
Summary - Background Mosquito-borne diseases are expanding their range, and re-emerging in areas where they had subsided - for decades. The extent to which climate change influences the transmission suitability and population at risk of - mosquito-borne diseases across different altitudes and population densities has not been investigated. The aim of this - study was to quantify the extent to which climate change will influence the length of the transmission season and - estimate the population at risk of mosquito-borne diseases in the future, given different population densities across - an altitudinal gradient. - Methods Using a multi-model multi-scenario framework, we estimated changes in the length of the transmission - season and global population at risk of malaria and dengue for different altitudes and population densities for the - period 1951-99. We generated projections from six mosquito-borne disease models, driven by four global circulation - models, using four representative concentration pathways, and three shared socioeconomic pathways. - Findings We show that malaria suitability will increase by 1·6 additional months (mean 0·5, SE 0·03) in tropical - highlands in the African region, the Eastern Mediterranean region, and the region of the Americas. Dengue suitability - will increase in lowlands in the Western Pacific region and the Eastern Mediterranean region by 4·0 additional - months (mean 1·7, SE 0·2). Increases in the climatic suitability of both diseases will be greater in rural areas than in - urban areas. The epidemic belt for both diseases will expand towards temperate areas. The population at risk of both - diseases might increase by up to 4·7 additional billion people by 2070 relative to 1970-99, particularly in lowlands and - urban areas. - Interpretation Rising global mean temperature will increase the climatic suitability of both diseases particularly in - already endemic areas. The predicted expansion towards higher altitudes and temperate regions suggests that - outbreaks can occur in areas where people might be immunologically naive and public health systems unprepared. - The population at risk of malaria and dengue will be higher in densely populated urban areas in the WHO African - region, South-East Asia region, and the region of the Americas, although we did not account for urban-heat island - effects, which can further alter the risk of disease transmission.
Gesehen am 20.10.2021